EVA implants for controlled drug delivery to the inner ear - Y. Bedulho das Lages; N. Milanino; J. Verin; J.F. Willart; F. Danede; C. Vincent; P. Bawuah; J.A. Zeitler; F. Siepmann; J. Siepmann (Elsevier, 2024)
This study evaluated the potential of poly(ethylene vinyl acetate) (EVA) copolymers as matrix formers in miniaturised implants, allowing to achieve controlled drug delivery into the inner ear. Due to the blood-cochlea barrier, it is impossible to reliably deliver a drug to this tiny and highly sensitive organ in clinical practice. To overcome this bottleneck, different EVA implants were prepared by hot melt extrusion, altering the vinyl acetate content and implant diameter. Dexamethasone was incorporated as a drug with anti-inflammatory and anti-fibrotic activity. Its release was measured into artificial perilymph, and the systems were thoroughly characterised before and after exposure to the medium by optical and scanning electron microscopy, SEM-EDX analysis, DSC, X-ray powder diffraction, X-ray microtomography and texture analysis. Notably, the resulting drug release rates were much higher than from silicone-based implants of similar size. Furthermore, varying the vinyl acetate content allowed for adjusting the desired release patterns effectively: With decreasing vinyl acetate content, the crystallinity of the copolymer increased, and the release rate decreased. Interestingly, the drug was homogeneously distributed as tiny crystals throughout the polymeric matrices. Upon contact with aqueous fluids, water penetrates the implants and dissolves the drug, which subsequently diffuses out of the device. Importantly, no noteworthy system swelling or shrinking was observed for up to 10 months upon exposure to the release medium, irrespective of the EVA grade. Also, the mechanical properties of the implants can be expected to allow for administration into the inner ear of a patient, being neither too flexible nor too rigid.